Analysis of Maslahah Mursalah on the Discourse of KUA Transformation as an Inclusive Religious Service in Indonesia - Riskianto, Ibadur; R. Tanzil Fawaiq Sayyaf (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
KUA is an important part of one of the technical implementers in the welfare of society in Indonesia, KUA aims to strive to achieve the vision and mission of the Ministry of Religion in realizing human resources who obey and comply with religious provisions along with the regulations made by the state. Thus, the transformation of the KUA is the right step in building maslahah through administration and transformation of the KUA as a place of implementation that can be done through the level of guidance and services at the family level to the community. Based on this, the focus of this research is to describe more broadly how the transformation values are capable of service efforts in all religions in Indonesia. The method used is skinatif-descriptive through library research. The results of this study, 1). The open response to the statement of the Minister of Religion (Menag) in the working meeting agreement with the Directorate General of Islamic Guidance (Bimas), 2). The meaning of transformation through services to all religions, 3). Preventive actions offered through the review of maslahah mursalah.